School Vouchers and Student Neighborhoods: Evidence from the Milwaukee Parental Choice Program - Carlson, Deven E.; Cowen, Joshua M. (Education Policy Analysis Archives, 2015)
In this paper we explore the relationship between students’ residential location and participation in Milwaukee’s large, widely available private school voucher program. We are interested in one overarching question: do voucher schools disproportionately draw students from better public schools and city neighborhoods, or do they draw students most in need of alternative options? We consider whether the public schools attended by students in neighborhoods contributing large numbers of students to the voucher program are more or less effective than those attended by students in neighborhoods with fewer voucher students. We also consider whether voucher students are located in city neighborhoods that directly contribute more or less to student outcomes. We find consistent evidence that neighborhoods whose students attend less effective public schools and neighborhoods with lower academic outcomes contribute disproportionately to the voucher program. This evidence is quite consistent with patterns apparent on Census-based observational measures of neighborhood socioeconomic characteristics: higher rates of voucher use are found in the least advantaged neighborhoods. We also find, however, that disadvantaged students in general are those most likely to leave the voucher program after enrolling.